Use of Gravimetric Separators for the Beneficiation of Gunduzler Chromite Ore - MALAYOGLU, U.; SEN, S.; Engin, V.T. (Asian Journal of Chemistry, 2010)
This study involves gravity processing of chromite samples taken from Eskisehir/Gunduzler ore deposit. Several gravity concentration tests including jig, shaking table and MGS concentration with different flowsheet options were performed for this purpose. The study revealed that a Cr2O3 rich concentrate high recovery values can be obtained by the application of gravity concentration techniques from this ore.